Shaping India’s EV future: a policy framework inspired by global best practices - Arindam Dutta; Sanjeevikumar Padmanaban (Academia Green Energy)
This study examines global electric vehicle (EV) policy approaches—driven by cost reduction, emission control, and energy security—to derive actionable insights for India’s EV transition. Through a comparative analysis of EV strategies in countries like China, Germany, the United States, Norway, Japan, Canada, and the Netherlands, this paper highlights how national priorities shape policy effectiveness. While India shows EV market potential with a projected 49% CAGR by 2030, it faces significant challenges, including policy gaps, limited charging infrastructure, and weak incentives. Drawing lessons from global leaders—such as Japan’s infrastructure-first approach and the Netherlands’ awareness campaigns—this study proposes a tailored roadmap for India. Recommendations include refining subsidies, enabling regulatory reforms, and expanding charging networks. The findings support India’s goal of 30% EV penetration by 2030, aligning with its broader climate commitments.